2013
DOI: 10.1002/anie.201206557
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Activity and Selectivity in Acid‐Catalyzed Reactions by Dealuminated Hierarchical Zeolites

Abstract: Shape‐selective reactions: Highly selective catalysts are obtained by alkaline and subsequent acid leaching of conventionally prepared zeolites. Active sites that are located in the shape‐selective environment of micropores and accessible through mesopores (see picture) provide high selectivity and activity in acid‐catalyzed reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 19 publications
0
41
1
Order By: Relevance
“…Pérez-Ramírez et al found that the mesoporosity of hierarchical zeolites can be tailored by partial detemplation of zeolites followed by desilication in alkaline medium. 143 In addition to the above demetallization methods, an irradiation route was developed by Valtchev et al to prepare hierarchical ZSM-5 zeolite with uniform parallel macropores that extended through the entire crystal. 142 Similar to dealumination, desilication inevitably modulates the framework Si/Al ratios; however, in this case it resulted in decreased Si/Al ratios.…”
Section: Desilicationmentioning
confidence: 99%
“…Pérez-Ramírez et al found that the mesoporosity of hierarchical zeolites can be tailored by partial detemplation of zeolites followed by desilication in alkaline medium. 143 In addition to the above demetallization methods, an irradiation route was developed by Valtchev et al to prepare hierarchical ZSM-5 zeolite with uniform parallel macropores that extended through the entire crystal. 142 Similar to dealumination, desilication inevitably modulates the framework Si/Al ratios; however, in this case it resulted in decreased Si/Al ratios.…”
Section: Desilicationmentioning
confidence: 99%
“…Conversely, the tetrahedral Al EF species formed during zeolite desilication in alkaline media are mobile and therefore exhibit a narrow symmetrical signal, [7] and Al EF species created upon steaming show an octahedral Al signal or are NMR-invisible.…”
Section: Samplementioning
confidence: 99%
“…Values of d i of around 60 ppm are typical for AlO 4 À tetrahedra in a zeolite environment. [6] The significant broad- Conversely, the tetrahedral Al EF species formed during zeolite desilication in alkaline media are mobile and therefore exhibit a narrow symmetrical signal, [7] and Al EF species created upon steaming show an octahedral Al signal or are NMR-invisible. [8] Thus, a terminal (SiO) 3 AlOH group, an analogue of silanol groups well-known in zeolites, [9] could explain the nature of the "perturbed" Al FR atoms.…”
mentioning
confidence: 99%
“…[26] While, the weaker Lewis acidity and more severe diffusion limitation on the ZSM-5 catalyst went against the transition etherification reaction. [27] Compared with the microporous zeolites, all of the hierarchical HSZ catalysts showed 100 % BHMF conversion and much higher BEMF selectivity. Because the acidity of the HSZ catalysts was much weaker than that of the two microporous ones, the only reason for the better performance of the HSZ catalysts might be that the mesoporous structure could facilitate the etherification reaction of BHMF and ethanol.…”
Section: Resultsmentioning
confidence: 97%
“…For the ROP products, more Brønsted acid sites on the ZSM‐5 catalyst would favor the reaction of ring‐opening . While, the weaker Lewis acidity and more severe diffusion limitation on the ZSM‐5 catalyst went against the transition etherification reaction …”
Section: Resultsmentioning
confidence: 99%